Dietary supplementation improves animal performance and reduces methane emission intensity in young llamas grazing natural forages - Ceron Cucchi, Maria Esperanza; Gere, José Ignacio; Chavarria, Nicolás José; Ramos, Nadia Elizabeth; Takahashi, Lumena S.; Montiel, María Delfina; Acuña, Francisco Antonio; Ortiz Chura, Abimael; Cravero, Silvio Lorenzo Pedro (Elsevier, 2025)
The aim of this study was to evaluate the effects of concentrate supplementation on animal performance, enteric methane (CH4) emissions, and forestomach (C1-C2 and C3) fermentative parameters of young llamas grazing on natural forage. Eighteen male llamas were assigned to two treatments, with 9 animals per treatment. The treatments were forage (F) with free access to natural grassland primarily composed of Festuca spp., and F plus supplement (FS). Supplementation with ground corn and soybean expeller (80:20 ratio on DM basis) was 1.5 % based on body weight for 35 days. The total dry matter intake (DMI), CH4 emissions (g/d), and CH4 yield (g/kg DMI) did not differ between diets. However, CH4 intensity (g/kg average daily gain) was significantly reduced (-48 %) in FS than in the F diet. The pH, total volatile fatty acids, and ammonia nitrogen concentrations in the C1-C2 did not differ between diets. However, the proportion of acetate and the acetate to propionate ratio decreased but propionate and butyrate were increased in the FS than in the F diet (P < 0.05). Whereas in C3, only butyrate increased in the FS diet than in the F diet (P < 0.05). Total bacteria and methanogen populations did not differ between treatments. Nevertheless, in C1-C2 and C3, the abundance of protozoa did differ statistically (P = 0.041 and P = 0.046, respectively), in the FS diet than in the F diet. In conclusion, concentrate supplementation increased propionate and butyrate proportions of forestomach contents which lead to improve animal performance and reduced CH4 emission intensity.